International and European Protection of the Right to Strike : A Comparative Study of Standards Set by the International Labour Organization, the Council of Europe and the European Union - Verge, Pierre (Relations industrielles / Industrial Relations, 2008)
The article reviews the book, "International and European Protection of the Right to Strike : A Comparative Study of Standards Set by the International Labour Organization, the Council of Europe and the European Union," by Tonia Novitz.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z